Dampak Kebijakan Harga Gabah dalam Meningkatkan Produksi Padi Indonesia - Laeli Sugiyono (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Statistika STIS, 2017)
This study aims to evaluate the elasticity of the floor grain price policy on domestic rice production. The analysis uses two stage least square regression. The study used secondary data from 1982 to 2013, which came from: BULOG, Ministry of Agriculture, BPS, and FAO. Research unit is Indonesian territory. The study concluded that the floor grain price has a significant positive effect on rice production with an elasticity of 0.034 in the short term and, 0.524 in the long term. This means that changes in the floor grain price in explaining domestic rice production are not elastic in the short term but are more elastic in the long run.